Aktivitas Analgesik dan Antiinflamasi Nanoemulsi Ekstrak Etanol Rimpang Kunyit (Curcuma longa L.) secara In Vivo - Recky Patala; Viani Anggi; Isna Paula; Nur Sakina (Journal of Pharmaceutical and Sciences, 2023)
Pain and Inflammation are our body's average protective measures. The presence of an inflammatory process is characterised by typical features, namely the appearance of redness, swelling in the area of inflammation, heat, and the onset of pain. One of the traditional plants widely obtained in Indonesia is Curcuma longa L. Curcuma longa L. contains flavonoid and curcumin compounds known to have analgesic and anti-inflammatory effects. The ethanol extract of Curcuma longa L. rhizome is formulated in nanoemulsion dosage form to reduce toxicity, improve drug distribution efficiency, and increase the bioavailability of drugs with low absorption. This study aims to determine the effect of the administration of nanoemulsion of ethanol extract of Curcuma longa L. at doses of 20 and 25 mg/kg bw on analgesic and anti-inflammatory activities carried out on male white rats of Wistar strain induced by 1% acetic acid and 1% carrageenan. Rats were divided into five groups (n=5), namely standard control (nanoemulsion without extract), positive control (mefenamic acid nanoemulsion for analgesic test and diclofenac sodium nanoemulsion for anti-inflammatory test), negative control (1% acetic acid nanoemulsion and 1% carrageenan nanoemulsion), P1 (extract nanoemulsion dose of 20 mg/kg bw), and P2 (extract nanoemulsion dose of 25 mg/kg bw). Furthermore, the number of writhing was measured from 5 to 60 minutes, and the leg volume changed from 1 to 6 hours. The results showed a decrease in the number of writhes with an increase in % Protection and significant inhibition of inflammation (p<0.05) in both doses of 20 mg/kg bw and 25 mg/kg bw with a per cent protection of 35.21% and a decrease in oedema volume by 64.79%. Nanoemulsion of Curcuma longa L. extract at doses of 20 and 25 mg/kg bw has activity as an analgesic and anti-inflammatory induced by 1% acetic acid and 1% carrageenan